Treatment of Dyes Industrial Effluents by Ionizing Radiation - Muneer, Majid; A. Bhatti, Ijaz; Nawaz Bhatti, Haq (Asian Journal of Chemistry, 2011)
The treatment of dyes wastewater by g-radiation is very efficient and simple method. In the present study wastewater samples were collected from ten dyes industries and were irradiated to the absorbed doses of 2, 5, 10 and 15 kGy using Co-60 g-radiation source. Before treatment effluents were highly polluted in term of colour intensity and chemical oxygen demand (COD) values. High energy radiation treatment has significantly improved the quality of polluted water, as its colour intensity reduced to 78 % at an absorbed dose of 15 kGy and almost complete colour removal was achieved when the samples were irradiated in the presence of hydrogen peroxide. Chemical oxygen demand decreased with the irradiation and its reduction was facilitated by irradiating the samples in presence of H2O2. Water quality parameters after irradiation were significantly improved. However, the treated wastewater of dyes industries could be utilized for agriculture and industrial reuse.